2019
DOI: 10.1039/c8nj05924a
|View full text |Cite
|
Sign up to set email alerts
|

Heterobimetallic copper(i) complexes bearing both 1,1′-bis(diphenylphosphino)ferrocene and functionalized 3-(2′-pyridyl)-1,2,4-triazole

Abstract: Copper(i) 1,1′-bis(diphenylphosphino)ferrocene complexes are well regulated by functional 3-(2′-pyridyl)-1,2,4-triazole exhibiting mono-anionic η2(N1,N2) and neutral η2(N1,N2) and η2(N1,N4) chelating modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 136 publications
1
9
0
Order By: Relevance
“…For the 3-(2′-pyridyl)-1,2,4-triazole-based Cu( i ) phosphine complexes, the HOMO mainly resides on the Cu and P atoms, and the LUMO is dominantly localized on the pyridyl segment of functional 3-(2′-pyridyl)-1,2,4-triazole. 63,68,70 The breaking of NH⋯O hydrogen bond increases the electron density on the triazolyl segment 82,83 but reduces that on the pyridyl segment, as supported by TD-DFT analyses ( vide infra ), which suggests that the breaking of NH⋯O hydrogen bond actually lowers the LUMO energy level mainly located on the pyridyl segment of 3-(2′-pyridyl)-1,2,4-triazole. A red-shifted emission in ground 1 (515 nm), relative to 1-G (500 nm), is thus attributed to the decrease of the LUMO level caused by the breaking of NH⋯O hydrogen bond under grinding.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…For the 3-(2′-pyridyl)-1,2,4-triazole-based Cu( i ) phosphine complexes, the HOMO mainly resides on the Cu and P atoms, and the LUMO is dominantly localized on the pyridyl segment of functional 3-(2′-pyridyl)-1,2,4-triazole. 63,68,70 The breaking of NH⋯O hydrogen bond increases the electron density on the triazolyl segment 82,83 but reduces that on the pyridyl segment, as supported by TD-DFT analyses ( vide infra ), which suggests that the breaking of NH⋯O hydrogen bond actually lowers the LUMO energy level mainly located on the pyridyl segment of 3-(2′-pyridyl)-1,2,4-triazole. A red-shifted emission in ground 1 (515 nm), relative to 1-G (500 nm), is thus attributed to the decrease of the LUMO level caused by the breaking of NH⋯O hydrogen bond under grinding.…”
Section: Resultsmentioning
confidence: 81%
“…[56][57][58][59][60] For Cu(I)-diiminephosphine system, the highest occupied molecular orbital (HOMO) is principally contributed by the Cu and P atoms, while the lowest unoccupied molecular orbital (LUMO) is largely located on the diimine. [61][62][63][64][65][66][67] If the diimine-NH used is prone to form hydrogen bonding with adjacent components such as anions, an orderly packing array can be easily formed under this weak interaction. Of course, this packing array is also easily destroyed by external forces.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that triazole compounds are used as corrosion inhibitors of organic copper, among which 1,2,4-triazole compounds are the most prominent. 36,37 However, 1,2,3-triazole has a good metal affinity with metal surfaces and are more vulnerable to attack by corresponding chemical entities than 1,2,4-triazoles. 33,38,39 Therefore, in this study, a novel triazole uorescence sensor is reported and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The high efficiency of photoluminescence and the potential for creating solution-processed organic light-emitting diodes have been shown [29][30][31][32][33][34][35][36][37]. On the example of complexes of pyridine-triazole with bis(diphenylphosphino)ferrocene, Chan and Chi et al have shown the possibility of the formation of both neutral (with ligand in a deprotonated form) and cationic complexes depending on the substituents in a heterocycle [38].…”
Section: Introductionmentioning
confidence: 99%